Parental knowledge of early childhood caries and its association with bottle-feeding practices: A cross-sectional analysis in the Riyadh Province, Saudi Arabia - Mohammed H. Alshamrani; Mohammed Ali Kharif; Naif Mohammed Alshayiqi; Ibrahim Ahmed Alqahtani; Belal Diri; Hashim Yasser Diri; Mohammed Alkithri; Mannaa K. Aldowsari (PLoS ONE, 2026)
Background Early childhood caries (ECC) remains a major public health concern globally and is highly prevalent in Saudi Arabia. Parental knowledge, attitudes, and feeding practices play a pivotal role in ECC prevention; however, data from the Riyadh region remain limited. Objective To assess parental knowledge and awareness of ECC and bottle-feeding attitudes among parents of children aged 1–5 years in the Riyadh region of Saudi Arabia. Methods A cross-sectional survey was conducted among 465 parents using a structured, self-administered questionnaire. The instrument assessed sociodemographic characteristics, knowledge of ECC, preventive oral health practices, and feeding behaviors. Knowledge scores were compared across demographic variables and feeding practices using bivariate analyses. Multivariable linear regression was performed to identify factors associated with knowledge. Results Overall parental knowledge was moderate, with notable gaps in awareness of early dental visits and early signs of ECC. While most parents recognized the importance of brushing primary teeth (82.8%) and restoring decayed primary teeth (65.6%), only 13.1% identified the recommended timing for the first dental visit. Night-time bottle feeding was highly prevalent (73.1%), and prolonged bottle use beyond one year was common (72.0%). Higher knowledge scores were significantly associated with brushing after bottle feeding (p < 0.001) and early cessation of bottle use (p = 0.038). Female gender, higher education, and higher household income were significantly associated with better knowledge (p < 0.05), although the model explained a modest proportion of variance (R² = 0.036). Conclusion Despite moderate overall awareness, substantial knowledge gaps and high-risk feeding practices persist among parents in the Riyadh region. Targeted, early, and culturally appropriate parental education integrated into maternal and pediatric healthcare and supported through digital platforms is essential to reduce the burden of ECC.